Cyclooxygenase inhibitors and the exercise-induced stress response - Claassen, N; Snyman, J; Koorts, A; Nolte, H; Wagenaar, B; Kruger, M; Becker, PJ; Viljoen, M (South African Journal of Sports Medicine, 2006)
Objective. This study investigated the effects of single dosages of the non-steroidal anti-inflammatory drug (NSAID) naproxen, and of the coxib, rofecoxib, on the exercise-induced stress response. Design. Eight subjects (age 20.9 ± 1.1 years, weight 70.4 ± 3.9 kg, height 170.9 ± 6.7 cm, body surface area 1.82 ± 0.09 m2, body mass index 24.1 ± 1.3 kg.m-2) took part in a double-blind, drug-placebo, cross-over design study. The experimental procedures were performed on 3 occasions on each volunteer, i.e. once on placebo, once on naproxen (single dose of 1 000 mg) and once on rofecoxib (single dose of 50 mg). Results. Mean post-exercise cortisol values were significantly higher than pre-exercise values with the subjects on placebo (p = 0.0365) and rofecoxib (p = 0.0208), but not on naproxen (p = 0.0732). Post-exercise oral temperatures were significantly higher than pre-exercise temperature values on placebo (p = 0.0153) and rofecoxib (p = 0.0424), but not on naproxen (p = 0.5444). Conclusion. The results of this study suggest a role for cyclooxygenase-1 (COX-1) in the exercise-induced cortisol and temperature response to exercise. South African Journal of Sports Medicine Vol. 18 (1) 2006: pp. 4-8